The Fluid Dynamic Basis for Actuator Disc and Rotor Theories - Gijs van Kuik (IOS Press, 2018)
The first rotor performance predictions were published by Joukowsky exactly 100 years ago. Although a century of research has expanded the knowledge of rotor aerodynamics enormously, and modern computer power and measurement techniques now enable detailed analyses that were previously out of reach, the concepts proposed by Froude, Betz, Joukowsky and Glauert for modelling a rotor in performance calculations are still in use today, albeit with modifications and expansions. This book is the result of the author's curiosity as to whether a return to these models with a combination of mathematics, dedicated computations and wind tunnel experiments could yield more physical insight and answer some of the old questions still waiting to be resolved. Although most of the work included here has been published previously, the book connects the various topics, linking them in a coherent storyline. This book will be of interest to those working in all branches of rotor aerodynamics - wind turbines, propellers, ship screws and helicopter rotors. It has been written for proficient students and researchers, and reading it will demand a good knowledge of inviscid (fluid) mechanics. Jens Nørkær Sørensen, DTU, Technical University of Denmark: "(...) a great piece of work, which in a consistent way highlights many of the items that the author has worked on through the years. All in all, an impressive contribution to the classical work on propellers/wind turbines." Peter Schaffarczyk, Kiel University of Applied Sciences, Germany: "(...) a really impressive piece of work!" Carlos Simão Ferreira, Technical University Delft: "This is a timely book for a new generation of rotor aerodynamicists from wind turbines to drones and personal air-vehicles. In a time where fast numerical solutions for aerodynamic design are increasingly available, a clear theoretical and fundamental formulation of the rotor-wake problem will help professionals to evaluate the validity of their design problem. 'The Fluid Dynamic Basis for Actuator Disc and Rotor Theories' is a pleasure to read, while the structure, text and figures are just as elegant as the theory presented." The cover shows 'The Red Mill', by Piet Mondriaan, 1911, collection Gemeentemuseum Den Haag. Cover image: © 2018 Mondrian/Holtzman Trust.